Tandemly repeated tRNA pseudogenes in photobacterium. - Giroux, S (Proc Natl Acad Sci U S A, 1988)
A region distal to three tRNA genes in Photobacterium phosphoreum, a Gram-negative eubacterium, unexpectedly contains a high number of repeated DNA segments that are closely related to the adjacent tRNAPro gene. The 5' to 3' order of this cluster is tRNAPro-tRNAHis-tRNAPro followed by eight tRNAPro-like structures interspersed by rho-independent terminators. The two tRNAPro genes, which are identical, and the tRNAHis gene have 86% and 87% positional identity, respectively, to their counterparts in the argT operon of Escherichia coli. The facts that these tRNA-like structures are not transcribed, in contrast to the tRNA retropseudogenes of eukaryotes, and that these structures are clustered near their progenitor suggest they are an unusual class of tRNA pseudogenes that arose by tandem duplication. IMAGES: